DETERMINASI MOTIVASI KOMPENSASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. SMOE INDONESIA. - Eneng Firdayanti; Indrayani Indrayani (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
This study aimed to analyzed the determination of motivation, compensation and communication on employee job performance. This study uses three independent variables, motivation, compensastion and communication, with one dependent variable namely performance. The use of variables in this study is expected to determine how the process is going on and what are the factors driving the creation of a good performance in the PT. SMOE Indonesia. Samples were employee in the PT SMOE Indonesia 100 people. Samples were taken by sampling techniques. Data analysis method used is quantitative analysis, the validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t-test, f-test the coefficient of determination R2.